Mn(III)-mediated bisphenol a degradation: Mechanisms and products. (15th May 2023) - Sun, Yanchen; Wang, Chao; May, Amanda L.; Chen, Gao; Yin, Yongchao; Xie, Yongchao; Lato, Ashley M.; Im, Jeongdae; Löffler, Frank E.
Highlights: Mn(III) associated with the surface of MnO2 contributes to BPA degradation. Mn(III)- and MnO2 -mediated degradation of BPA differ mechanistically. Mechanistic differences lead to products with distinct toxicological profiles. Mn(III)-mediated BPA degradation should be considered in natural attenuation assessments. Abstract: Bisphenol A (BPA) is a high production volume chemical with potential estrogenic effects susceptible to abiotic degradation by MnO2 . BPA transformation products and reaction mechanisms with MnO2 have been investigated, but detailed process understanding of Mn(III)-mediated degradation has not been attained. Rapid consumption of BPA occurred in batch reaction vessels with 1 mM Mn(III) and 63.9 ± 0.7% of 1.76 ± 0.02 μmol BPA was degraded in 1 hour at circumneutral pH. BPA was consumed at 1.86 ± 0.09-fold higher rates in vessels with synthetic MnO2 comprising approximately 13 mol% surface-associated Mn(III) versus surface-Mn(III)-free MnO2, and 10–35% of BPA transformation could be attributed to Mn(III) during the initial 10-min reaction phase. High-resolution tandem mass spectrometry (HRMS/MS) analysis detected eight transformation intermediates in reactions with Mn(III), and quantum calculations proposed 14 BPA degradation products, nine of which had not been observed during MnO2 -mediated BPA degradation, suggesting mechanistic differences between Mn(III)- versus MnO2 -mediated BPA degradation. The findings demonstrate that both Mn(III) and Mn(IV) can effectively degrade BPA and indicate that surface-associated Mn(III) increases the reactivity of synthetic MnO2, offering opportunities for engineering more reactive oxidized Mn species for BPA removal. Graphical abstract: Image, graphical abstract